Assessment of quality of life among caregivers of persons with permanent disabilities attending rehabilitation centre in H. D. Kote Taluq, Mysore district, Karnataka, India - Boralingiah, Prakash; Baby, Arun; Kulkarni, Praveen; Ramachandrappa, Seetharam M.; Manjunath, Renuka (International Journal Of Community Medicine And Public Health, 2016)
Background: Quality of life (QoL) is defined as “an individual’s perception of their position in life in the cultural context and in the value systems in which they live and in relation to their goals, expectations, concerns and desires. Caregivers of persons with chronic health conditions run the risk of emotional distress and poor adjustment to the demands of the patient, which in turn may adversely affect the quality of care that a person in need would receive. An assessment of quality of life among caregivers is important, for interventions targeted at rehabilitation. Methods: A 100 caregivers of persons with disability registered under the rehabilitation program of SVYM at VMH Saragur were selected for the study. WHOQOL-BREF questionnaire was used to assess quality of life of caregivers. Results: The Mean age of the caregivers was found to be 38.25 years with 87 (87%) females and 13 (13%) males. The mean Quality of Life of these caregivers was 71.97. Physical domain was significantly associated with income, earning capacity and duration of care. Psychological domain was associated with income and family type. Social domain was the most affected, with factors viz. Age (p-value=0.002), employment (p-value=0.02), earning capacity (p-value=0.032), education and duration of care being significantly associated. Environmental domain was associated with relation to caregiver, earning capacity (p-value=0.032), education and income. Marital status was observed to affect all the domains. Conclusions: The Quality of Life of Caregivers was significantly affected by a multitude of factors which need to be addressed to ensure proper care of their wards. Interventions aimed at building the capacities the affected individuals as well as the caregivers would be highly beneficial to both groups.